The Influence of Self Efficacy, Work Environment and Organizational Culture on Employee Performance at the Bangkalan Pratama Tax Office - Lela Kurniawati; Kuswandi; Sri Rahayu; Rifda Fitrianty (International Publisher, 2025)
This study was conducted to examine employee performance based on the influence of Self Efficacy, work environment and organizational culture. The sample in this study were 77 employees at the Bangkalan Primary Tax Service Office. The analytical tool used is multiple linear regression. The results showed that partially the Self Efficacy variable, work environment and organizational culture had a positive and significant effect on employee performance. Then the results of simultaneous testing of self efficacy variables, work environment and organizational culture affect employee performance, at the Bangkalan Pratama Tax Service Office, East Java.